Diversity of firm sizes, complexity, and industry structure in the Chinese economy - Torsten Heinrich; Shuanping Dai (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2015)
Among the phenomena in economics that are not yet well-understood is the fat-tailed (power-law) distribution of firm sizes in the worlds economies. Different mechanisms suggested in the literature to explain this distribution of firm sizes are discussed in the present paper. The paper uses the China Industrial Enterprises Database to study the distribution (firm size in terms of the number of employees, capital, and gross profit) for the provinces of China for the years 1998-2008. We estimate the power-law distribution and confirm its plausibility using the KS test and the log-likelihood ratio vs. lognormal and exponential distributions. The analysis on regional levels allows an assessment of regional effects on differences in the distribution; we discuss possible explanations for the observed patterns in the light of the recent regional economic development in the PRC.
Keywords: 330; firm size distribution; evolutionary industry dynamics; power-law distribution; China